2021
DOI: 10.1097/dss.0000000000003126
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Role of Mohs Micrographic Surgery in the Management of Early-Stage Melanoma of the Head and Neck

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…[22][23][24][25]28,29 Typically, MIS is treated with 5-mm excision margins, but difficulties can arise when MIS is located in sun-exposed regions. 30 The systematic review of 32 articles published by Theunissen et al 31 showed that MMS had lower local recurrence rates for early-stage melanomas compared with staged excision and WLE: pooled recurrence risk 0.8% (95% CI 0.4-1.1) vs. 2.5% (95% CI 1.5-3.4) vs. 8.7% (95% CI 5.1-12.2) (P = 0.001), respectively. Similarly, Nosrati et al 32 (n = 662) found overall recurrence rates of 1.8% for MMS compared with 5.7% for WLE (P = 0.07) for MIS.…”
Section: Melanoma In Situ and Lentigo Malignamentioning
confidence: 99%
“…[22][23][24][25]28,29 Typically, MIS is treated with 5-mm excision margins, but difficulties can arise when MIS is located in sun-exposed regions. 30 The systematic review of 32 articles published by Theunissen et al 31 showed that MMS had lower local recurrence rates for early-stage melanomas compared with staged excision and WLE: pooled recurrence risk 0.8% (95% CI 0.4-1.1) vs. 2.5% (95% CI 1.5-3.4) vs. 8.7% (95% CI 5.1-12.2) (P = 0.001), respectively. Similarly, Nosrati et al 32 (n = 662) found overall recurrence rates of 1.8% for MMS compared with 5.7% for WLE (P = 0.07) for MIS.…”
Section: Melanoma In Situ and Lentigo Malignamentioning
confidence: 99%
“…An evolving body of literature continues to demonstrate higher cure rates, lower local recurrence rates, and equivalent or superior survival for melanoma treated with Mohs micrographic surgery (MMS) compared with staged excision (SE), and/or wide local excision (WLE). 1–8 A recent systematic review and meta-analysis that compiled the largest dataset to date for head and neck melanoma (HNM) showed lower overall recurrences when treating melanoma in situ (MIS) and invasive melanoma with MMS or SE compared with WLE. 7 Another recent systematic review concluded MMS has a lower local recurrence rate for early-stage melanoma over SE and WLE.…”
mentioning
confidence: 99%
“…7 Another recent systematic review concluded MMS has a lower local recurrence rate for early-stage melanoma over SE and WLE. 8 However, only a minority of Mohs surgeons treat melanoma with MMS. 9–15 Given that general dermatologists play a vital role in treating and referring patients with melanoma, this nationwide cross-sectional survey sought to investigate the practice habits and referral preferences of general dermatologists regarding MMS for treating melanoma on the head and neck.…”
mentioning
confidence: 99%
“…1 Data have emerged supporting this practice, highlighting lower rates of recurrence with Mohs and complete circumferential peripheral and deep margin assessment over conventional wide local excision. [2][3][4][5] Specific practice patterns vary, as do outcomes among treatment facilities with differing volumes. 6 With these discrepancies come a calling for standardization of best practices.…”
mentioning
confidence: 99%